PENGARUH PENERAPAN BAHAN AJAR FISIKA BERMUATAN KARAKTER DALAM STRATEGI PEMBELAJARAN STUDENT RECAP TERHADAP HASIL BELAJAR SISWA KELAS VIII SMPN 12 PADANG - Mulya Suci Utari (Universitas Negeri Padang, 2014)
The background of this research are still many students who received learning outcomes defined under standard. One reason for the use of teaching materials of physics that has not integrated the value of the character. This study aimed to investigate the effect of the application of physics teaching materials the character charged recap student learning strategies on learning strategies on learning outcomes of students of class VIII SMPN 12 Padang. This type of research is a Quasi-Experimental design with randomized control group only design and its population all the student of grade VIII in SMPN 12 Padang enrolled in the academic year 2013/2014. The sample is selected by purposive sampling technique. The sample is consisted of VIII.6 as the experimental class and the control class VIII.7 as the number of members of the same sample. The research instrument is the ultimate test for cognitive learning outcomes, assessment sheets for affective learning outcomes affective, and psychomotor assessment sheets for psychomotor domains of learning outcomes. Analysis of data uses two common test average on the real level of 0,05 to the result of cognitive learning, affective, and psychomotor. The result show of research is hypothesis that there are significant adoption of instructional materials in the physics of charged character recap student learning strategies on learning outcomes of students of class VIII SMPN 12 Padang was about the real level of 0,05